Understanding the role of public preferential procurement on the development of black owned construction SMME'S IN South Africa - Nzo, Khulile (Graduate School of Business (GSB), 2021)
The research explored the long-term relationship between FDI, GDP and host country employment by using sector-wise panel data from 1991 to 2017 in Namibia. The study applied unit root testing and Cointegration test to test for the presence of a cointegration relationship between the variables. Also, a vector autoregression model short-run causality among the variables was examined. In the end, Impulse response functions are estimated. The research found both a short term and long-term causality going from FDI inflow to employment. Impulse responses show that both GDP and employment respond positively to an exogenous shock in FDI inflow. However, the employment response to FDI inflow shock is smaller than that of GDP response. The paper also concludes that FDI has no causal effects on economic growth in Namibia. It means that economic growth is not contributed by the FDI significantly the results in this research have some significant policy implications. Therefore, as the results suggest that the FDI inflow has a positive impact on employment, because of the results, the researcher also recommends that Namibia pursue the policy of attracting foreign firms aggressively and create all the conditions required for attracting foreign direct investment in order to create further employment opportunities.